More Purpose in Life and Less Novelty Seeking Predict Improvements in Self-Compassion During a Mindfulness-Based Intervention: The EXMIND Study - Akase, Mari; Terao, Takeshi; Kawano, Nobuko; Sakai, Akari; Hatano, Koji; Shirahama, Masanao; Hirakawa, Hirofumi; Kohno, Kentaro; Ishii, Nobuyoshi (Frontiers in Psychiatry, 2020)
Objectives: Recently, a four-week mindfulness-based intervention followed by a four-week existential approach was found to be as effective for increasing self-compassion as an eight-week mindfulness-based intervention. The purpose of the present study was to identify the factors that predicted change in self-compassion during the eight-week mindfulness-based intervention. Methods: Fifty-seven of the 61 completers of the eight-week mindfulness-based intervention provided baseline, four-week, and eight-week Self-Compassion Scale (SCS) scores. The mean age of the 47 females and 10 males was 49.6 years. Pearson’s correlation coefficients were generated on the associations between the change of total SCS scores from baseline to eight weeks with age; gender; and the baseline scores on the Temperament Evaluation of Memphis, Pisa and San Diego Auto-questionnaire, Temperament and Character Inventory (TCI), Mini-Mental State Examination, Japanese Adult Reading Test, Young Mania Rating Scale, Hamilton Rating Scale for Depression, Parental Bonding Instrument, and purpose in life (PIL). Multiple regression analysis was performed to identify the predictors of the change in total SCS scores. Results: Novelty seeking (TCI) was significantly and negatively associated with the change in total SCS scores, whereas the purpose in life (PIL) scores were significantly and positively associated with the change in total SCS scores. Novelty seeking was not significantly associated with baseline, four-week, or eight-week total SCS scores, whereas the PIL scores were significantly and positively associated with baseline, four-week, and eight-week total SCS scores. Conclusions: The present findings suggest that more purpose in life and less novelty seeking predict improvements in self-compassion during mindfulness-based interventions, although novelty seeking might substantially predict the improvement but SCS and PIL might somewhat conceptually overlap.